Spraying film material for tunnel and preparation method of spraying film material
Through the combination of specific proportion of acrylic components and modified minerals, the spray material for tunnel is prepared, solving the problem of insufficient weather resistance in existing materials in the outdoor environment, and realizing excellent waterproof and weather resistance. Essence
Patent Information
- Application Number
- CN202411619608.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-21
AI Technical Summary
The existing acrylate spray film waterproofing materials have poor weather resistance in outdoor environments and are difficult to meet the waterproofing needs of tunnels and other places.
It uses a specific proportion of acrylic acid, methacrylic acid, N-hydroxyethylacrylamide and diethylenetriamine and other ingredients, combined with modified bentonite and modified silicon carbide, and undergoes sodiumization and impregnation modification treatments to prepare a product with excellent waterproof properties. and weather-resistant spray film materials.
This spray material does not seep water at 120 minutes at a pressure of 0.4MPa. After alkali and salt treatment, it still maintains high stretch strength and elongation rate, which significantly improves waterproof performance and weather resistance.
Smart Images

Figure BDA0005133097200000041 
Figure BDA0005133097200000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building engineering materials, and in particular to a spray film material for a tunnel and a preparation method thereof. Background Art
[0002] A large number of engineering practices have shown that water is a key factor affecting the safety, durability, stability and use of buildings; long-term rainwater erosion will cause steel bars to rust, reduce their strength and rigidity, and threaten personal safety. In order to avoid building leakage problems, waterproof and anti-seepage construction technology should be reasonably used in construction projects to improve the overall anti-seepage performance of building structures, extend their service life and avoid safety accidents.
[0003] Acrylate spray film waterproof material is a new type of polymer waterproof material with acrylate as the main component. It can be rapidly polymerized into a three-dimensional mesh structure within 1 to 5 seconds under the catalytic action of a curing agent, thereby achieving efficient waterproofing. However, some existing acrylate spray film waterproof materials have poor weather resistance and are not suitable for waterproofing requirements in outdoor environments such as tunnels. Therefore, providing an acrylate spray film waterproof material with high weather resistance for use in tunnels has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0004] The purpose of the present invention is to provide a spray film material for a tunnel and a preparation method thereof, wherein the spray film material for a tunnel has excellent waterproof performance and weather resistance.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A spray film material for tunnels comprises the following raw materials in parts by weight: 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-10 parts of N-hydroxyethyl acrylamide, 5-10 parts of diethylenetriamine, 180-220 parts of modified bentonite, 40-60 parts of modified silicon carbide, 2-5 parts of dispersant, 2-5 parts of defoamer and 290-310 parts of water.
[0008] Preferably, the spray film material for tunnels comprises the following raw materials in parts by mass: 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoaming agent and 300 parts of water.
[0009] Furthermore, the preparation method of the modified bentonite comprises the following steps:
[0010] 1) mixing NaOH and Na2CO3 to obtain a bentonite sodium agent;
[0011] 2) placing bentonite in water and stirring to form slurry, then adding bentonite sodiumizing agent to sodiumize the bentonite to obtain sodiumized bentonite, i.e. the modified bentonite.
[0012] Furthermore, in step 1), the mass ratio of NaOH to Na2CO3 is 1:(2-3).
[0013] Furthermore, in step 2), the mass ratio of the bentonite, water and bentonite sodium agent is 1:9:(0.1-0.3).
[0014] Furthermore, in step 2), the sodiumization is specifically: stirring the sodiumization at 40-60° C. for 2-4 hours.
[0015] Furthermore, in step 2), after the sodiumization is completed, it is necessary to filter, wash with dilute hydrochloric acid until neutral, and dry.
[0016] Furthermore, the preparation method of the modified silicon carbide comprises the following steps:
[0017] 1) performing sintering treatment and aging treatment on silicon carbide in sequence to obtain sintered modified silicon carbide;
[0018] 2) placing the sintered modified silicon carbide obtained in step 1) in a NaOH solution for impregnation modification to obtain impregnated modified silicon oxide, i.e. the modified silicon carbide.
[0019] Furthermore, in step 1), the sintering treatment is specifically: sintering at 1320-1350° C. for 30-50 min.
[0020] Furthermore, in step 1), the aging treatment is specifically: aging treatment at 100-150° C. for 2-3 hours.
[0021] Furthermore, in step 1), the aging treatment is followed by grinding and passing through an 800-mesh sieve.
[0022] Furthermore, in step 2), the concentration of the NaOH solution is 0.5 mol·L -1 .
[0023] Furthermore, in step 2), the mass volume ratio of the sintered modified silicon carbide and the NaOH solution is 1 g: 20 mL.
[0024] Furthermore, in step 2), the impregnation modification is specifically: impregnation modification at 120-150° C. for 20-40 minutes.
[0025] The second technical solution of the present invention:
[0026] The method for preparing the above-mentioned spray film material for tunnels comprises the following steps:
[0027] Acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine are added to water and mixed, then a dispersant and a defoamer are added and mixed, and finally modified bentonite and modified silicon carbide are added and mixed to obtain the spray film material for tunnels.
[0028] The third technical solution of the present invention:
[0029] The above-mentioned spray film material for tunnels is used in tunnel waterproofing.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The spray film material for tunnels provided by the present invention is tested for water seepage at 0.4 MPa for 120 minutes and is water-proof, thus having excellent waterproof performance.
[0032] The spray film material for tunnels provided by the present invention has a tensile strength of 1.1 MPa and an elongation at break of 465% after alkali treatment, and has a tensile strength of 1.0 MPa and an elongation at break of 468% after salt treatment, and has excellent weather resistance. DETAILED DESCRIPTION
[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] In the following examples, all the raw materials used are commercially available, as shown in Table 1;
[0039] Table 1 Raw materials and specifications
[0040]
[0041] In the following embodiments, a method for preparing a spray film material for a tunnel comprises the following steps:
[0042] 1) mixing NaOH and Na2CO3 in a mass ratio of NaOH to Na2CO3 of 1:(2-3) to obtain a bentonite sodium agent;
[0043] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:(0.1-0.3), stirring to form a slurry, then adding the bentonite sodium agent, stirring at 40-60° C. for 2-4 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e., modified bentonite;
[0044] 3) sintering the silicon carbide at 1320-1350° C. for 30-50 min, then aging at 100-150° C. for 2-3 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0045] 4) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 3) is placed in a solution with a concentration of 0.5 mol·L -1 In a NaOH solution, at 120-150°C, the impregnation modification is carried out for 20-40 minutes to obtain impregnated modified silicon oxide, i.e. modified silicon carbide;
[0046] 5) Weigh each raw material according to the following mass parts:
[0047] 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-10 parts of N-hydroxyethyl acrylamide, 5-10 parts of diethylenetriamine, 180-220 parts of modified bentonite, 40-60 parts of modified silicon carbide, 2-5 parts of dispersant, 2-5 parts of defoamer and 290-310 parts of water;
[0048] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 5) are added to the water weighed in step 5), and stirred for 40 minutes. Then, the dispersant and defoamer weighed in step 5) are added, and stirred for 1 hour. Finally, the modified bentonite and modified silicon carbide weighed in step 5) are added, and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0049] Example 1
[0050] A spray film material for tunnel
[0051] 1) mixing NaOH and Na2CO3 in a mass ratio of 1:2 to obtain a bentonite sodium agent;
[0052] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:0.1, stirring to form a slurry, then adding bentonite sodium agent, stirring at 40°C for 2h, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e. modified bentonite;
[0053] 3) sintering the silicon carbide at 1320° C. for 30 min, then aging at 100° C. for 2 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0054] 4) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 3) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 120°C for 20 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0055] 5) Weigh each raw material according to the following mass parts:
[0056] 140 parts of acrylic acid, 20 parts of methacrylic acid, 5 parts of N-hydroxyethyl acrylamide, 5 parts of diethylenetriamine, 180 parts of modified bentonite, 40 parts of modified silicon carbide, 2 parts of dispersant, 2 parts of defoamer and 290 parts of water;
[0057] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 5) are added to the water weighed in step 5), and stirred for 40 minutes. Then, the dispersant and defoamer weighed in step 5) are added, and stirred for 1 hour. Finally, the modified bentonite and modified silicon carbide weighed in step 5) are added, and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0058] Example 2
[0059] A spray film material for tunnel
[0060] 1) mixing NaOH and Na2CO3 in a mass ratio of 1:2.5 to obtain a bentonite sodium agent;
[0061] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:0.2, stirring to form a slurry, then adding bentonite sodium agent, stirring at 50°C for 3 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e., modified bentonite;
[0062] 3) sintering the silicon carbide at 1340° C. for 40 min, then aging at 120° C. for 2.5 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0063] 4) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 3) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 130°C for 30 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0064] 5) Weigh each raw material according to the following mass parts:
[0065] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0066] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 5) are added to the water weighed in step 5), and stirred for 40 minutes. Then, the dispersant and defoamer weighed in step 5) are added, and stirred for 1 hour. Finally, the modified bentonite and modified silicon carbide weighed in step 5) are added, and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0067] Example 3
[0068] A spray film material for tunnel
[0069] 1) mixing NaOH and Na2CO3 in a mass ratio of 1:3 to obtain a bentonite sodium agent;
[0070] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:0.3, stirring to form a slurry, then adding bentonite sodium agent, stirring at 60°C for 4 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e. modified bentonite;
[0071] 3) sintering the silicon carbide at 1350° C. for 50 min, then aging at 150° C. for 3 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0072] 4) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 3) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 150°C for 40 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0073] 5) Weigh each raw material according to the following mass parts:
[0074] 160 parts of acrylic acid, 30 parts of methacrylic acid, 10 parts of N-hydroxyethyl acrylamide, 10 parts of diethylenetriamine, 220 parts of modified bentonite, 60 parts of modified silicon carbide, 5 parts of dispersant, 5 parts of defoamer and 310 parts of water;
[0075] 6) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 5) are added to the water weighed in step 5), and stirred for 40 minutes. Then, the dispersant and defoamer weighed in step 5) are added, and stirred for 1 hour. Finally, the modified bentonite and modified silicon carbide weighed in step 5) are added, and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0076] Comparative Example 1
[0077] A spray film material
[0078] 1) sintering silicon carbide at 1340° C. for 40 min, then aging at 120° C. for 2.5 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0079] 2) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 4) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 130°C for 30 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0080] 3) Weigh each raw material according to the following mass parts:
[0081] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0082] 4) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 3) are added to the water weighed in step 3) and stirred for 40 minutes, then the dispersant and defoamer weighed in step 3) are added and stirred for 1 hour, and finally the bentonite and modified silicon carbide weighed in step 3) are added and stirred for 30 minutes to obtain the spray film material.
[0083] Comparative Example 2
[0084] A spray film material
[0085] 1) placing bentonite in water according to the mass ratio of bentonite, water and bentonite sodium agent (Na2CO3) of 1:9:0.2, stirring to form a slurry, then adding the bentonite sodium agent, stirring at 50°C for 3 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e. modified bentonite;
[0086] 2) sintering the silicon carbide at 1340° C. for 40 min, then aging at 120° C. for 2.5 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0087] 3) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 2) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 130°C for 30 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0088] 4) Weigh each raw material according to the following mass parts:
[0089] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0090] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 4) are added to the water weighed in step 4) and stirred for 40 minutes, then the dispersant and defoamer weighed in step 4) are added and stirred for 1 hour, and finally the modified bentonite and modified silicon carbide weighed in step 4) are added and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0091] Comparative Example 3
[0092] A spray film material
[0093] 1) placing bentonite in water according to the mass ratio of bentonite, water and bentonite sodium agent (NaOH) of 1:9:0.2, stirring to form a slurry, then adding the bentonite sodium agent, stirring at 50°C for 3 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e. modified bentonite;
[0094] 2) sintering the silicon carbide at 1340° C. for 40 min, then aging at 120° C. for 2.5 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide;
[0095] 3) According to the sintering modified silicon carbide and the concentration of 0.5mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and the sintered modified silicon carbide obtained in step 2) is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 130°C for 30 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0096] 4) Weigh each raw material according to the following mass parts:
[0097] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0098] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 4) are added to the water weighed in step 4) and stirred for 40 minutes, then the dispersant and defoamer weighed in step 4) are added and stirred for 1 hour, and finally the modified bentonite and modified silicon carbide weighed in step 4) are added and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0099] Comparative Example 4
[0100] A spray film material
[0101] 1) mixing NaOH and Na2CO3 in a mass ratio of 1:2.5 to obtain a bentonite sodium agent;
[0102] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:0.2, stirring to form a slurry, then adding bentonite sodium agent, stirring at 50°C for 3 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e., modified bentonite;
[0103] 3) According to silicon carbide and concentration of 0.5 mol·L -1 The mass volume ratio of the NaOH solution is 1g:20mL, and silicon carbide is placed in a solution with a concentration of 0.5 mol·L -1 The modified silicon carbide is prepared by immersing in a NaOH solution at 130°C for 30 minutes to obtain an impregnated modified silicon oxide, i.e., modified silicon carbide;
[0104] 4) Weigh each raw material according to the following mass parts:
[0105] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0106] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 4) are added to the water weighed in step 4) and stirred for 40 minutes, then the dispersant and defoamer weighed in step 4) are added and stirred for 1 hour, and finally the modified bentonite and modified silicon carbide weighed in step 4) are added and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0107] Comparative Example 5
[0108] A spray film material
[0109] 1) mixing NaOH and Na2CO3 in a mass ratio of 1:2.5 to obtain a bentonite sodium agent;
[0110] 2) placing bentonite in water in a mass ratio of bentonite, water and bentonite sodium agent of 1:9:0.2, stirring to form a slurry, then adding bentonite sodium agent, stirring at 50°C for 3 hours, filtering, washing with dilute hydrochloric acid until neutral, and drying to obtain sodium bentonite, i.e., modified bentonite;
[0111] 3) sintering the silicon carbide at 1340° C. for 40 min, then aging at 120° C. for 2.5 h, grinding, and passing through an 800-mesh sieve to obtain sintered modified silicon carbide, i.e., modified silicon carbide;
[0112] 4) Weigh each raw material according to the following mass parts:
[0113] 150 parts of acrylic acid, 25 parts of methacrylic acid, 7 parts of N-hydroxyethyl acrylamide, 7 parts of diethylenetriamine, 200 parts of modified bentonite, 50 parts of modified silicon carbide, 3 parts of dispersant, 3 parts of defoamer and 300 parts of water;
[0114] 5) The acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine weighed in step 4) are added to the water weighed in step 4) and stirred for 40 minutes, then the dispersant and defoamer weighed in step 4) are added and stirred for 1 hour, and finally the modified bentonite and modified silicon carbide weighed in step 4) are added and stirred for 30 minutes to obtain the spray film material for the tunnel.
[0115] Effect verification
[0116] Referring to Q / CR 517.1-2017, the spray film materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for weather resistance. The results of the weather resistance test are shown in Table 2.
[0117] Table 2 Weathering performance test results
[0118]
[0119] It can be seen from the data in Table 2 that the spray film material for tunnels prepared by the present invention is water-proof after a water seepage test at 0.4 MPa for 120 min, and has excellent waterproof performance;
[0120] It can be seen from the data in Table 2 that the spray film material for tunnels prepared by the present invention has a tensile strength of 1.1 MPa and an elongation at break of 465% after alkali treatment, and has a tensile strength of 1.0 MPa and an elongation at break of 468% after salt treatment, and has excellent weather resistance. It can be seen from Comparative Examples 1 to 5 that omitting the modification of bentonite, omitting NaOH in the bentonite sodium agent, omitting Na2CO3 in the bentonite sodium agent, omitting the sintering modification of silicon carbide, and omitting the impregnation modification of silicon carbide will all reduce the weather resistance of the spray film material to a certain extent.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A spray film material for tunnels, characterized in that: The invention comprises the following raw materials in parts by weight: 140-160 parts of acrylic acid, 20-30 parts of methacrylic acid, 5-10 parts of N-hydroxyethyl acrylamide, 5-10 parts of diethylenetriamine, 180-220 parts of modified bentonite, 40-60 parts of modified silicon carbide, 2-5 parts of dispersant, 2-5 parts of defoaming agent and 290-310 parts of water.
2. The spray film material for tunnel according to claim 1, characterized in that: The preparation method of the modified bentonite comprises the following steps: 1) mixing NaOH and Na2CO3 to obtain a bentonite sodium agent; 2) placing bentonite in water and stirring to form slurry, then adding bentonite sodiumizing agent to sodiumize the bentonite to obtain sodiumized bentonite, i.e. the modified bentonite.
3. The film spraying material for tunnel according to claim 2, characterized in that: In step 1), the mass ratio of NaOH to Na2CO3 is 1:(2-3).
4. The film spraying material for tunnel according to claim 2, characterized in that: In step 2), the mass ratio of the bentonite, water and bentonite sodium agent is 1:9:(0.1-0.3); the sodiumization is specifically carried out by stirring at 40-60° C. for 2-4 hours.
5. The film spraying material for tunnel according to claim 1, characterized in that: The preparation method of the modified silicon carbide comprises the following steps: 1) performing sintering treatment and aging treatment on silicon carbide in sequence to obtain sintered modified silicon carbide; 2) placing the sintered modified silicon carbide obtained in step 1) in a NaOH solution for impregnation modification to obtain impregnated modified silicon oxide, i.e. the modified silicon carbide.
6. The film spraying material for tunnel according to claim 5, characterized in that: In step 1), the sintering treatment is specifically: sintering treatment at 1320-1350° C. for 30-50 min; the aging treatment is specifically: aging treatment at 100-150° C. for 2-3 h.
7. The spray film material for tunnel according to claim 5, characterized in that: In step 2), the concentration of the NaOH solution is 0.5 mol·L -1 ; The mass volume ratio of the sintered modified silicon carbide and the NaOH solution is 1g:20mL; the impregnation modification is specifically: impregnation modification at 120-150°C for 20-40min.
8. A method for preparing a spray film material for a tunnel as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Acrylic acid, methacrylic acid, N-hydroxyethyl acrylamide and diethylenetriamine are added to water and mixed, then a dispersant and a defoamer are added and mixed, and finally modified bentonite and modified silicon carbide are added and mixed to obtain the spray film material for tunnels.
9. Use of the spray film material for tunnels as claimed in any one of claims 1 to 7 in tunnel waterproofing.